Livelihood strategies for communities in drought prone areas: a case of Mwenezi district Zimbabwe - Tembo, Sandra Samantha (Midlands State University, 2017)
The study focused on the investigation of the livelihood strategies of people living in Mwenezi district. The study looks at the challenges in implementing the livelihood strategies. lt identified the vulnerabilities to drought that people face in Mwenezi. lnterviews were conducted and each respondent from a selected household was asked questions and responses were organized so that conclusions can be drawn. The study also attempted to highlight challenges of drought in Mwenezi. Agriculture and the economies in Sub Saharan Africa are highly sensitive to climatic variability. Drought in particular represents one of the most important natural factors contributing to malnutrition and famine in many parts of region .Literature has shown that drought has been the most devastating condition that poses the greatest natural hazard. The study went on to investigate the sustainability and effects of the livelihood strategies implemented in Mwenezi. The overall study findings show that despite having increased livelihood interventions in Mwenezi, the extent to which they contributed to livelihood improvement was limited. The study shows that despite the decline in agricultural production, it remains the major livelihood activity. Agricultural activities such as small grain production and livestock rearing experienced a decline but were partially revived through external support from both the third sector and the government.